Cyber security, cyber crime and cyber forensics : applications and perspectives - Santanam, Raghu, 1969-; Sethumadhavan, M., 1966-; Virendra, Mohit (Hershey, PA : Information Science Reference, 2011)
"This book provides broad coverage of technical and socio-economic perspectives for utilizing information and communication technologies and developing practical solutions in cyber security, cyber crime and cyber forensics"--Provided by publisher.
Includes bibliographical references (p. 259-286) and index.
Keywords: Computer security; Cyberspace -- Security measures; Computer crimes; Computer crimes -- Investigation